2010
DOI: 10.1002/ppap.201000019
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Carbon Nanotubes by Corona‐Discharge Induced Graft Polymerization for the Reinforcement of Epoxy Nanocomposites

Abstract: Corona discharge treatment at atmospheric pressure was applied to initiate the graft polymerization of 2‐hydroxyethyl methacrylate onto the surface of multi‐walled carbon nanotubes (MWCNTs). The results indicated that MWCNTs were encapsulated by poly(2‐hydroxyethyl methacrylate) (PHEMA). The blue shift and the increased ID/IG value of the Raman spectra confirmed the covalent attachment of PHEMA onto the surface of the MWCNTs. The grafting degree depended on the processing time of corona discharge, as demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Compared with the Raman spectra of pure MWNTs, the slight difference in the line shape and blueshift of the G band of MWNTs in the MTA composite indicate the thiol grafting of MWNTs in the composite resins, [ 30 ] which is similar to the previous studies of CNT functionalization with polymers. [ 31,32 ] In this work, the thiol molecules are believed to be anchored to the MWNT surfaces, forming covalent functionalization of the MWNTs ( Figure S3, Supporting Information). It is reported that the strong attachment of the polymers to CNTs induces the observed blueshift of G band in Raman spectroscopy due to the increase in the elastic constant of the harmonic oscillators of the polymer-coated MWNTs.…”
Section: It Is Diffi Cult To Develop Tpp-compatible Photoresists Withmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared with the Raman spectra of pure MWNTs, the slight difference in the line shape and blueshift of the G band of MWNTs in the MTA composite indicate the thiol grafting of MWNTs in the composite resins, [ 30 ] which is similar to the previous studies of CNT functionalization with polymers. [ 31,32 ] In this work, the thiol molecules are believed to be anchored to the MWNT surfaces, forming covalent functionalization of the MWNTs ( Figure S3, Supporting Information). It is reported that the strong attachment of the polymers to CNTs induces the observed blueshift of G band in Raman spectroscopy due to the increase in the elastic constant of the harmonic oscillators of the polymer-coated MWNTs.…”
Section: It Is Diffi Cult To Develop Tpp-compatible Photoresists Withmentioning
confidence: 98%
“…It is reported that the strong attachment of the polymers to CNTs induces the observed blueshift of G band in Raman spectroscopy due to the increase in the elastic constant of the harmonic oscillators of the polymer-coated MWNTs. [ 32,33 ] Moreover, the thiolacrylic polymers provide additional carbon source which may contribute to the defect repairing of the embedded MWNTs during the annealing process, thus leading to a reduced I D / I G ratio after thermal annealing of the MTA composite ( Figure S4, Supporting Information). A Raman mapping image of a "TPP" pattern fabricated by TPP lithography was obtained using the G-band intensity mapping at each pixel, showing the distribution of MWNTs in the microstructures (Figure 2 b).…”
Section: It Is Diffi Cult To Develop Tpp-compatible Photoresists Withmentioning
confidence: 98%
“…These methods range from low pressure plasmas to atmospheric plasmas, such as corona discharge to dielectric barrier discharge, etc. [18][19][20][21][22]. Utilizing plasma methods to treat or modify nanomaterials can widen the range of polymer matrix possibilities, and studying/tailoring those coatings/modifications can increase the nanofillers's dispersion in polymer matrices and enhance the filler/matrix interfacial bonding in order to achieve the desired properties of the resulted polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [96] reported the reinforcement of epoxy nanocomposites with poly-(2-hydroxyethyl methacrylate) (PHEMA)-grafted CNTs (PHEMA-g-CNTs). Figure 2.24 shows the flexural moduli of the epoxy/PHEMA-g-CNT nanocomposites as a function of CNT content.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It is known that the mechanical performance of epoxy/CNT composites strongly depends on the uniformity of nanotube dispersion within the polymer matrix and the strong interfacial interactions between the two components [95,96,120]. It has been shown that functionalized CNTs are more readily dispersed in an epoxy matrix and have better interfacial interactions, which is beneficial for improving the properties of the composites [105].…”
Section: Mechanical Propertiesmentioning
confidence: 99%